Description of School Health Development Index (SHDI) in Junior High Schools in Buleleng Regency – Bali - Dharmadi, Made Agus; Agustini, Ni Nyoman Mestri (KEMAS: Jurnal Kesehatan Masyarakat, 2019)
Synergism in the field of health and education is strongly needed and urgent in order to attain a comprehensive education goal of intelligent and healthy people both physically and mentally according to the mandate of the 1945 Constitution. Based on the observation in Junior High Schools in Buleleng, We found that there were a lack synchronization between vision, missions, and the planned programs in the schools, limited cleaning facilities, and an implicitly lack of healthy lifestyle of the school residents. This research aimed to describe the School Health Development Index (SHDI) at the level of secondary schools in Buleleng Regency in 2017. The sample of the research were obtained from 10 junior high schools/JHS (SMP) in Buleleng Regency. We used a method of quantitative description following observations, documentation studies, and interviews. Based on the result and discussion, we concluded that: 1) SHDI of SMP in Buleleng Regency was categorized as mid-low (0.62), with minimal value of 0.51 and largest value of 0.78. The highest index was obtained by SMP 1 Singaraja and the lowest index was obtained by SMP Bhaktiasa Singaraja, 2) most of the schools did not include healthy value explicitly in the schools’ vision and missions, 3) most of the schools operated limited number of programs on health and did not include written reports on their programs, 4) the condition of facilities and infrastructures were sufficient, there were several schools having no warehouse, and the food products in cafeterias were not controllable yet especially for the unlicensed food products (without BPOM logo), 4) the school residents’ healthy lifestyle was good enough especially for the teachers and the students.